دور المهرجانات الثقافية في تحسين كفاءة التسويق السياحي دراسة ميدانية على المنشآت السياحية في محافظة طرطوس - برهوم, أديب; سليمان, نبيلة; حسن, علا محمود (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يهدف البحث إلى تعرف دور المهرجانات الثقافية في تحسين كفاءة التسويق السياحي من خلال دراسة العلاقة بين سياحة المهرجانات الثقافية و(التنمية السياحية, والمزيج التسويقي, وتحسين كفاءة الأنشطة التسويقية, والحد من موسمية السياحة). اعتمدت الباحثة على المنهج الوصفي التحليلي, وتمّ بناء استبانة تتكون من (40) فقرة وخمسة محاور أساسية, وشملت عينة البحث (101) منشأة سياحية من المنشآت العاملة في محافظة طرطوس تم سحبها بطريقة عشوائية. وبعد الدراسة والتحليل توصل البحث إلى النتائج التالية: 1- وجود وعي كبير لدى العاملين في المنشآت السياحية حول أهمية سياحة المهرجانات الثقافية والدور الذي تلعبه في التنميّة السياحيّة، والمزيج التسويقي، بالإضافة إلى دورها في تحسين كفاءة الأنشطة التسويقيّة. 2- يؤكد العاملون في المنشآت السياحية على أن المهرجانات الثقافية تؤثر في كفاءة الأنشطة التسويقية من خلال قياس مدى تحقق الأهداف التسويقية, وإسهامها في تحقيق ربحية الأنشطة التسويقية, من خلال زيادة الحركة السياحية الداخلية, وتمكنها من زيادة الإنتاج من خلال تنمية المرافق وتطويرها, وتأثيرها في فعالية المنشأة السياحية من خلال زيادة النشاط الثقافي وتنشيطه, وإسهامها في تحسين كفاءة الأنشطة التسويقية من خلال تقديم المنتج السياحي المتكامل. 3- وجود علاقة ارتباط طردية وذات دلالة معنوية بين سياحة المهرجانات وكل من (التنمية السياحية, والمزيج التسويقي, وتحسين كفاءة الأنشطة التسويقية السياحية, والحد من موسمية السياحة), حيث إن تنشيط سياحة المهرجانات الثقافية يلعب دوراً كبيراً في تنمية كفاءة الأنشطة التسويقية السياحية وتحسينها. The research aims to identify the role of cultural festivals in improving the efficiency of tourism marketing through the study of the relationship between tourism and cultural festivals (tourism development, the marketing mix, improve the efficiency of marketing activities, and the reduction of seasonal tourism). The researcher relied on descriptive analytical method, which built a questionnaire consisting of 40 items and five key areas. The research sample includes (101) of the property's establishments operating in the province of Tartous and it was pulled in a random manner. After the study and analysis, the most important results are: 1 –There is of a large awareness among workers in the tourist facilities on the importance of tourism and cultural festivals role in tourism development, and marketing mix, in addition to its role in improving the efficiency of marketing activities. 2- Workers in tourist facilities confirm that cultural festivals affect the efficiency of marketing activities by measuring the extent of marketing objectives, and its range contribution to the profitability of marketing activities, through increasing tourist traffic Interior, and enabling them to increase production through the development of facilities, and their impact on the effectiveness of the property by increasing the revitalization of the cultural movement, and its contribution to improving the efficiency of marketing activities through the provision of integrated tourism product. 3 -The presence of positive correlation and significant correlation between tourism festivals and all of the (tourism development, marketing mix, improve the efficiency of marketing activities of tourism, and the reduction of seasonal tourism), as the revitalization of tourism cultural festivals plays a big role in the development and improves the efficiency of marketing tourist activities.